Peranan Kampung Angklung Ciamis dalam Revitalisasi Seni Musik Tradisional Sunda di Era Modern - Restu Aulia Amanda; Resma Alfiani Azzahra; Dita Amalia Agustin (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
Globalization and popular culture have posed significant challenges to the sustainability of traditional arts, including Sundanese music. Kampung Angklung Ciamis is a community-based cultural space that plays an important role in preserving and revitalizing traditional Sundanese music, particularly angklung. This article aims to analyze the role of Kampung Angklung Ciamis in the modern revitalization of this traditional music. The study employs a descriptive approach using field research, collecting data via observation, interviews, and documentation. The findings indicate that Kampung Angklung Ciamis functions not only as a center for cultural preservation but also as an agent of cultural revitalization through cultural education, intergenerational transmission, active community participation, and creative adaptation of angklung music to contemporary contexts. The study further shows that the revitalization of traditional music is a dynamic and contextual process rather than a static one. The sustainability of angklung music is strongly influenced by the active involvement of local communities in responding to social and cultural change. These findings emphasize the importance of community-based cultural initiatives in sustaining intangible cultural heritage in the modern era.